Susanne B. Wilson at a ground breaking ceremony - Unknown:::Creator::::::::::::
Photograph shows Susanne B. Wilson walking across an empty lot carrying a shovel. There is a small crowd behind her including Lois Cullison who is the women in the pale coat on the far left. This may be a ground breaking ceremony for the YWCA's building on 375 S. Third Street which opened in 1975.